(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Modern communication devices are no longer used merely for text or voice communication, now a days, it is also in extensive use for entertainment. With the advancement of the technology, the communication devices are now turning to multipurpose smart devices like i-phone, smart phone and many other mobile devices. These multipurpose devices are capable of providing various entertaining functions to its users, likewise, a general form of entertainment in communication devices has been popular that is known as mobile game. A mobile game is one that can be run for user entertainment on the common platforms presently used in modern portable communication devices. In this project, we have designed and developed a mobile game, named The Avoider, which is capable of running on JAVA based portable device platforms. Generically, this game belongs to the category of Adventure Games and uses a straightforward AI strategy in order to achieve user entertainment. We have chosen the geographical area of Chittagong University of Engineering & Technology as the strategic platform of the game, where a user has to travel through from one end to the other and face a number of enemies attacking him. Options have been left for the user to move his/her hero in a four-directional manner in order to save it from the attacks of enemy. The game has been developed using Java 2 Micro Edition (J2ME) standard and the cellular phones or portable communication devices that support this standard can install and enjoy this game. Â Keywords: Design, Implementing, Avoider, Measurement, Performance, Mobile Gaming, Titles, Hero, Enemies, Animation.